Development of Service-Based Film Media to Stimulate Social Care, Critical Thinking, Creative, and Collaborative Skills - Ashshiddieqy, Kanzenna Kurnia; Untari, Sri; Al-Atok, A Rosyid; Nafsiyah, Fitrotun (Edukasi, 2024)
The purpose of this study was to develop service-learning-based short film media to improve critical, creative, collaborative, and social care skills. Test validity, test practicality, and test effectiveness used ADDIE model flows. The analysis stage obtained the characteristics of learners, curriculum analysis and learning resources. The design stage was carried out the development of short film media. The development stage was carried out validity tests and practicality tests. At the implementation stage, effectiveness tests were carried out. The evaluation phase was carried out. Data collection tools used were material and media validation instruments, interview instruments, instruments for prospective teacher and student users, and performance self-assessment test sheets. data analysis using Shapiro-Wilk Technique and Paired Samples T-Test. This film had gone through validation tests by several validators, and the results were declared feasible, interesting, and valid for use in learning. The media validation score reached 57.5, being in the range of 60-48.75, with very valid criteria for subsequent studies. Material validation achieved a validity score of 95.5, being in the range of 96-78, with very valid criteria. The teacher user candidate test showed a validity score of 68 out of a maximum score of 68, which when calculated as a percentage, indicated a validity score of 100% in the range of 68-55.25. Small group trials gave a score of 518 from the range of 600-487.5, while large group trials gave a score of 2,186 from the range of 2460-1998.75. The paired sample T-test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05.